Quality Analysis of Grade 6 Literacy and Numeracy End-of-Semester Exam Questions Based on Classical Test Theory - Prasetyani, Kusumaningrum; Laras Ati, Luri; Shokib Rondli, Wawan; Kanzunnudin, Mohammad (JGSD: Jurnal Guru Sekolah Dasar, 2024)
This study aims to analyze the quality of literacy and numeracy end-of-semester exam questions for grade 6 SD Negeri 3 Pojok, Tawangharjo sub-district based on Classical Test Theory. The research method used is quantitative by analyzing the validity, reliability, difficulty level, and differentiating power of the questions. The research sample consisted of 10 6th grade students of SD Negeri 3 Pojok. The data was collected through documentation of student answer sheets in the final semester exam. Data analysis was conducted using Anates program. The results showed that out of 30 items, there were 22 valid questions and 8 invalid questions. The reliability coefficient of the question is 0.82 which is included in the high category. The level of difficulty of the questions consisted of 10 easy questions, 15 medium questions, and 5 difficult questions. The differentiating power of the questions consisted of 5 bad questions, 10 fair questions, 10 good questions, and 5 excellent questions. It can be concluded that the quality of literacy and numeracy end-of-semester exam questions for grade 6 of SD Negeri 3 Pojok, Tawangharjo sub-district is classified as good based on Classical Test Theory.